Legal Syncretism in Practice: Acculturation of Islamic and Customary Norms in the Tunggu Tubang Marriage Tradition of Semende - Solihan, Solihan; Izomiddin, Izomiddin; Mohammad Syawaludin; Kiki Mikail; Padila, Padila (Nurani: jurnal kajian syari'ah dan masyarakat, 2025)
This research explores how local cultural values and Islamic principles blend within the Tunggu Tubang marriage tradition practiced by the Semende community in Muara Enim Regency. The methodology employed encompasses sociological, philosophical, and legal approaches, with data collection conducted through interviews and a literature review related to socio-cultural phenomena and religious texts. The findings indicate that acculturation is a social process through which elements of foreign culture are accepted and integrated into local culture without the loss of their original identity.  Within the Tunggu Tubang tradition, Islamic values and local customs are applied in a complementary manner, allowing both to coexist and be sustained over time. Traditions such as the giving of parbiye and the recognition of the eldest daughter’s role as Tunggu Tubang are acknowledged and respected, reflecting the complex relationship between customary law and Islamic law.  This research also identifies the challenges and opportunities involved in maintaining cultural identity amidst modernity, highlighting the crucial roles of customary institutions and community leaders in safeguarding traditions. The findings offer valuable insight into the way Islamic principles and local traditions, especially the Tunggu Tubang marriage practice in Semende interact and evolve, shaping a social framework deeply rooted in both cultural heritage and religious meaning.